The Effect of Quality of Work Life on Employee Performance with Organizational Commitment and Job Satisfaction as Intervening Variables at the Department of Social Work and Labor Yogyakarta City Transmigration - Putri, Yanita Primadani; Winarno, Winarno; Ambarwati, Sri Dwi Ari (UPN Veteran Yogyakarta, 2023)
The results of the evaluation of the State Organization of the Republic of Indonesia and the Accountability System of Government Agencies (SAKIP), the strengthening of Bureaucratic Reform by the Kemenpan-RB in the field of social welfare, the social performance of the Dinsosnakertrans of Yogyakarta City for 3 consecutive years is very volatile and has never reached the target of 100 points. The purpose of this study is to determine whether or not there is a direct effect of the quality of work life on the performance of Dinsosnakertrans employees, and to determine the indirect effect of the quality of work life on employee performance through organizational commitment and job satisfaction. The research method used is quantitative method. The sample size is calculated using the Non-probability technique (saturated sample), and a sample of 68 employees is obtained. The analytical technique used is descriptive analysis, which aims to describe the demographic data of the respondents, and quantitative analysis using Simple Regression Analysis to see the direct effect, and Path Analysis for the mediated indirect effect. The results show that QWL directly has a positive and significant effect on employee performance. QWL indirectly has no significant effect on employee performance variables through organizational commitment. QWL indirectly, has no significant effect on employee performance variables through employee satisfaction .Keywords: Job Satisfaction, Employee Performance, Organizational Commitment, Quality Work Life